2020
DOI: 10.1002/hed.26324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lymph node ratio and lymph node yield as prognosticators of locoregional recurrence in p16‐associated oropharyngeal squamous cell carcinoma

Abstract: Background The prognostic value of lymph node yield (LNY) and lymph node ratio (LNR), or the ratio of number of metastatic LNs to total number dissected, has not been well established in p16‐associated oropharyngeal squamous cell carcinoma (OPSCC). Methods This retrospective cohort study evaluated locoregional disease‐free survival (LRDFS) in 82 patients with p16+ OPSCC who underwent neck dissection at a single institution from 2009 to 2017. LNR and LNY cutoffs were estimated using time‐dependent receiver oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(60 reference statements)
0
1
1
Order By: Relevance
“…The number of detected elective lymph nodes in this study was similar to a previous study that examined the MRI visibility and displacement of lymph nodes during radiotherapy in HNC patients (level Ib: 5 vs. 5, level II: 18 vs. 21, level III: 8 vs. 11, level IV: 2 vs. 7 and level V: 6 vs. 8) [15] . Pathology studies that investigated neck dissections in HNSCC patients reported a lymph node yield varying from 34 to 46 [18] , [19] , [20] , [21] on each side of the neck, which is higher than the number of lymph nodes seen in the present study. However, in the present study lymph nodes with a maximal transverse diameter < 4 mm, lymph nodes suspect for containing metastases, and lymph nodes only visible in one MRI slice were excluded.…”
Section: Discussioncontrasting
confidence: 81%
“…The number of detected elective lymph nodes in this study was similar to a previous study that examined the MRI visibility and displacement of lymph nodes during radiotherapy in HNC patients (level Ib: 5 vs. 5, level II: 18 vs. 21, level III: 8 vs. 11, level IV: 2 vs. 7 and level V: 6 vs. 8) [15] . Pathology studies that investigated neck dissections in HNSCC patients reported a lymph node yield varying from 34 to 46 [18] , [19] , [20] , [21] on each side of the neck, which is higher than the number of lymph nodes seen in the present study. However, in the present study lymph nodes with a maximal transverse diameter < 4 mm, lymph nodes suspect for containing metastases, and lymph nodes only visible in one MRI slice were excluded.…”
Section: Discussioncontrasting
confidence: 81%
“…Pathology studies reported a lymph node yield between 34 and 45 in (modified) radical neck dissections on each side of the neck (level Ib-V) ( 13 16 ). We reported a lower number of lymph nodes in these levels.…”
Section: Discussionmentioning
confidence: 99%